2020
DOI: 10.1186/s13071-020-3964-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of proteins from the secretory/excretory products (SEPs) of the branchiuran ectoparasite Argulus foliaceus (Linnaeus, 1758) reveals unique secreted proteins amongst haematophagous ecdysozoa

Abstract: Background: It is hypothesised that being a blood-feeding ectoparasite, Argulus foliaceus (Linnaeus, 1758), uses similar mechanisms for digestion and host immune evasion to those used by other haematophagous ecdysozoa, including caligid copepods (e.g. sea louse). We recently described and characterised glands associated with the feeding appendages of A. foliaceus using histological techniques. The work described in the present study is the first undertaken with the objective of identifying and partially charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 103 publications
(134 reference statements)
0
7
0
Order By: Relevance
“…Intracellular serpins may have various functions, from the inhibition of anti-coagulatory proteases to enhancing lysosome stability [ 19 , 55 ]. Intracellular serpins were detected in the excretory product of blood-feeding parasites such as ticks [ 13 , 14 ], or in the saliva of the fish ectoparasite arthropod, Argulus foliaceus [ 56 ]. These studies concluded that intracellular serpins are supposed to be one of the major components involved in evasion of the host defense mechanisms for successful feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular serpins may have various functions, from the inhibition of anti-coagulatory proteases to enhancing lysosome stability [ 19 , 55 ]. Intracellular serpins were detected in the excretory product of blood-feeding parasites such as ticks [ 13 , 14 ], or in the saliva of the fish ectoparasite arthropod, Argulus foliaceus [ 56 ]. These studies concluded that intracellular serpins are supposed to be one of the major components involved in evasion of the host defense mechanisms for successful feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrolases have been identi ed from different parasite venoms which are known to include proteases, peptidases and glycosidase enzymes [34,35]. As we have not only identi ed hydrolase transcripts here in Argulus tissues, but also recently in Argulus SEPs through proteomic analysis [11], the presence of hydrolases might re ect their contribution to host-parasite interactions in Argulus species. The identi ed metalloproteases from different arthropods are assumed to be related to different biological processes such as digestion, cuticle degradation and host immune suppression [47].…”
Section: Discussionmentioning
confidence: 83%
“…As there is no reference genome for Argulus, the transcriptomes of both A. foliaceus and A. coregoni were assembled de novo using Trinity v2.1.1 software. The assembled transcriptomes are important for both genomic and proteomic studies [11], especially in terms of providing the complete ORF information for genes coding for proteins that may play important roles in biological processes and might therefore provide potentially suitable vaccine candidates [12] or targets for anti-parasiticides.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations